Diákok élelmiszerfogyasztási szokásainak vizsgálata nemzetközi viszonylatban - Panyor, Ágota; Lendvai, Edina; Gál, József (Jelenkori Társadalmi és Gazdasági Folyamatok, 2014)
The present study examines the context of a competition won (Leonardo da Vinci), the young people’s eating habits. Within the framework of research online questionnaire we filled up with students from the countries participating in the project, including 465 evaluable substances. In our study, we analyzed the students’ preferences and food consumption of traditional foods and their motivations for fast food.